2022
DOI: 10.1186/s12888-022-04252-z
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and challenges faced by community mental health workers when providing care to people with mental illness: a qualitative study

Abstract: Background Mental illness is a major burden of disease worldwide. Community Mental Health Services (CMHS) are key to achieving community-based recovery for people with mental illness. In China, even though the community management of patients with mental illness is improving, the barriers faced by Community Mental Health Workers (CMHWs) are unclear. This study explores the difficulties and challenges in CMHS from the perspective of CMHWs. The results of this study may provide a practical basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…On the other hand, Taylor et al (2021) contend that when CHWs are seen as bearers of more and more roles and tasks, this also means that they are focused on current work tasks without proactively identifying new needs [ 47 ]. Additionally, their broad responsibilities and lack of expertise leave CHWs ambiguous about their job roles and make them feel overwhelmed and powerless [ 48 ]. Workload overload, insufficient first aid knowledge and skills, and lack of professional support limited CHWs' willingness to deliver FA training to older adults in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Taylor et al (2021) contend that when CHWs are seen as bearers of more and more roles and tasks, this also means that they are focused on current work tasks without proactively identifying new needs [ 47 ]. Additionally, their broad responsibilities and lack of expertise leave CHWs ambiguous about their job roles and make them feel overwhelmed and powerless [ 48 ]. Workload overload, insufficient first aid knowledge and skills, and lack of professional support limited CHWs' willingness to deliver FA training to older adults in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This poor distribution of attention can further stimulate negative emotions such as depression, anxiety, and helplessness [48] . At the same time, interpersonal communication skills being impaired are detrimental to establishing a trusting relationship between caregivers and patients and increase work stress [49] . As the screening rate of social withdrawal and SD among college students gradually increases, it will seriously affect the mental health development of nursing students [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Their negative opinions of such occupations [15], stress, and emotional weariness are factors in their lack of care in working in psychiatric settings [16]. In psychiatric settings, more than half of the nurses are said to experience significant stress and emotional exhaustion [17]. In addition, research found that nursing beginners are unwilling to work in mental facilities because of mental anguish, a range of workrelated stresses, and adverse public impressions of such environments.…”
Section: Ranian R Ehabilitation Journalmentioning
confidence: 99%